Registros recientes de los puercoespines, género Coendou (Mammalia: Erethizontidae) para el departamento de Córdoba, Colombia (2016)
Recent records of porcupines, Coendou quichua and Coendou prehensilis are reported for the department of Córdoba, in the Caribbean region of Colombia. These are from the southern part of the department, from remote regions and the buffer area of the Paramillo National Nature Park. The locality reported here is the seventh verified for the country. Illegal trafficking of one individual of C. prehensilis was observed and comments on its use and threats it faces on a national level are given.